Exploring the Antioxidant Potential of Blackberry and Raspberry Leaves: Phytochemical Analysis, Scavenging Activity, and In Vitro Polyphenol Bioaccessibility - Iulia Varzaru; Alexandra Gabriela Oancea; Petru Alexandru Vlaicu; Mihaela Saracila; Arabela Elena Untea (Antioxidants, 2023)
The goal of this research was nutritional evaluation through the phytochemical analysis of blackberry and raspberry leaves, the screening of their biological activity (antioxidant capacity and inhibition of lipid peroxidation), and the investigation of the effect of in vitro gastrointestinal digestion (GID) of blackberry and raspberry leaves on the bioaccessibility of polyphenol subclasses. The concentrations of the analyzed liposoluble antioxidants were higher (p < 0.05) in blackberry leaves compared to raspberry leaves, while a significant (p < 0.05) higher content of water-soluble antioxidants was registered in raspberry leaves (with a total polyphenol content of 26.2 mg GAE/g DW of which flavonoids accounted for 10.6 mg/g DW). Blackberry leaves had the highest antioxidant capacity inhibition of the superoxide radicals (O2•−), while raspberry leaves registered the highest inhibition of hydroxyl radicals (•OH), suggesting a high biological potency in scavenging-free radicals under in vitro systems. The maximum inhibition percentage of lipid peroxidation was obtained for blackberry leaves (24.86% compared to 4.37% in raspberry leaves), suggesting its potential to limit oxidative reactions. Simulated in vitro digestion showed that hydroxybenzoic acids registered the highest bioaccessibility index in the intestinal phase of both types of leaves, with gallic acid being one of the most bioaccessible phenolics. The outcomes of this investigation reveal that the most significant release of phenolic compounds from blackberry and raspberry leaves occurs either during or after the gastric phase. Knowledge about the bioaccessibility and stability of polyphenol compounds during digestion can provide significant insights into the bioavailability of these molecules and the possible effectiveness of plant metabolites for human health.